2011
DOI: 10.1103/physrevb.83.155327
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of freestanding silicon nanocrystals probed with electron spin resonance of interfacial dangling bonds

Abstract: The oxidation of freestanding silicon nanocrystals (Si-NCs) passivated with Si-H bonds has been investigated for a wide range of oxidation times (from a few minutes to several months) by means of electron spin resonance (ESR) of dangling bonds (DBs) naturally incorporated at the interface between the NCs core and the developing oxide shell. These measurements are complemented with surface chemistry analysis from Fourier-transform infrared spectroscopy. Two surface phenomena with initiation time thresholds of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
107
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(120 citation statements)
references
References 73 publications
10
107
1
Order By: Relevance
“…In previous work, we found that oxidation follows the Cabrera-Mott mechanism with a characteristic time t m = 14.4 min [40]. Based on this oxidation mechanism, we can investigate the dependence of the localization length on the separation s between NCs.…”
Section: Si4 Oxidationmentioning
confidence: 99%
“…In previous work, we found that oxidation follows the Cabrera-Mott mechanism with a characteristic time t m = 14.4 min [40]. Based on this oxidation mechanism, we can investigate the dependence of the localization length on the separation s between NCs.…”
Section: Si4 Oxidationmentioning
confidence: 99%
“…An extremely low defect density (7×10 9 cm −2 ) is found for Si-NCs grown with additional hydrogen gas injected into the afterglow region of the plasma, hereafter referred to as low initial defect density (LIDD) Si-NCs. We also compare the process of oxidation in air of the LIDD Si-NCs with that of Si-NCs containing an order of magnitude larger initial defect density (MIDD Si-NCs mentioned above), addressed in a previous study, 25 which have been grown without injection of hydrogen gas into afterglow region of the plasma. No change of defect density during the induction period is observed for the LIDD Si-NCs.…”
mentioning
confidence: 99%
“…Si-db reduction upon air exposure was observed for these MIDD Si-NCs during the so-called induction period, before creation of defects initiated by surface oxide shell growth. 25 After complete oxidation the density of defects saturates at a value of 5×10 10 cm −2 . 25 Comparatively, Si-NCs grown from microwave plasma-assisted decomposition of silane 2 display typically one order of magnitude higher density of interfacial Si-dbs (5-7×10 11 cm −2 ) after surface oxidation in air is completed, 19,24 corresponding to 0.25-0.35 defects per NC for Si-NCs with 4 nm in size.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is well-recognized that the oxidation of silicon nanocrystals usually follows the Cabrera-Mott mechanism, 29,30 as supported by previous investigations. [31][32][33] This mechanism describes how a Si crystal surface is oxidized by the simultaneous presence of water and oxygen molecules in the ambient air. Specifically, the polar water molecules approach the surface silanol groups preferentially and aid in the cleavage of Si-Si bonds adjacent to the silanol groups.…”
Section: -14mentioning
confidence: 99%